The Uncertain Path to Enterprise Architecture (EA) Maturity in the South African Financial Services Sector - Bachoo, Avsharn (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2018)
The research described in this article used the resource-based view (RBV) of the firm as an underlying theoretical framework to explore the relationship between enterprise architecture (EA) maturity and associated business value in the South African financial services environment. EA maturity was examined as an intangible resource and as a source of heterogeneity. The study identified the capabilities of business units at different levels of EA maturity, and found that EA is implemented at a coarse-grain level at lower organisational levels, and at finer-grain levels as one moves up the maturity curve. The study also found that EA is a source of both tangible and intangible forms of business value.
Keywords: resource-based view (RBV), enterprise architecture (EA), enterprise architecture (EA) maturity, financial services, business value, tangible business value, intangible business value, South Africa